Broadening our Perspectives: Health of Women and Children Globally. Issue 3 (May 2017) - N/A,
Abstract : Dr. Callister, as guest editor of this MCN special topics series on global health, presents a summary of the importance of nursing contributions to the wellbeing of mothers and children worldwide as highlighted in the feature articles and emphasizes the critical health needs of this vulnerable population.